Urbanization without structural transformation in Accra, Ghana - Williams Ohemeng; Abdul Malik Iddrisu; George Domfe; Michael Danquah (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2024)
This paper draws on quantitative and qualitative analyses to examine the patterns of structural transformation, the drivers and constraints of structural transformation, and how the configuration of power within the city and its interactions with national and city political settlements affects structural transformation in Accra, Ghana. Using data from the Ghana Integrated Business and Establishment Survey, the findings show that spatial variation in establishments matters in Accra. The share of establishments and employment in manufacturing and tradable services is low while that in the services sector dominates in all municipalities. The labour productivity estimates for Accra show that there is heterogeneity in labour productivity across municipalities, sectors, sizes of enterprises, and formality. Only a few municipalities positively correlate with labour productivity. Municipalities with relatively high politically competitive regimes experience high levels of labour productivity. This is attributed to politicians seeking to maximize votes in politically competitive areas, while ruling governments tend to increase the provision of infrastructure and services in these municipalities at the detriment of other areas that may critically require such infrastructure. The dominance of the service sector in Accra is connected to the city and national political settlements. This is because the activities in wholesale trade and service sectors rather than manufacturing seem to favour the political and business elites because of the quick, lucrative returns and profits. The growth in this sector means the availability of rents to fund and run election campaigns and maintain their ruling coalition.
Keywords: 330; urbanization; structural transformation; political settlement; Accra; Ghana